Emphysematous Cystitis with Bladder Mass caused by Colovesical Fistula: A Rare Case Report - Yosi Rizal; Eka Yudha Rahman (Fakultas Kedokteran Universitas Brawijaya, 2023)
Emphysematous cystitis (EC) is a rare manifestation of a complicated urinary tract infection, and its pathognomonic feature is a gas appearance inside the bladder wall and lumen. Emphysematous cystitis with bladder mass is an extremely rare finding. In this case study, a 59-year-old female presented with dysuria and pneumaturia for two months before admission. Following history taking and physical examination, a CT scan was performed to establish the diagnosis, which revealed thickening bladder wall with free gas appearance, impressing emphysematous cystitis. Urine culture showed no bacterial growth, cystoscopy revealed posterosuperior bladder mass, a biopsy was done followed by fulguration of the bladder and showed no malignancy, and MRI implied emphysematous cystitis with bladder dome adhesions of colon mass with colovesical fistula. After resection of colon anastomosis, colitis was found as the etiology of the colovesical fistula. An accurate diagnosis of the disease and correct treatment would result in a good prognosis and outcome.